Improve food, water, and economic benefits in China’s oases through crop switching - Peng Chen; Shuai Wang; Yanxu Liu; Qiang Tang; Yijia Wang; Jiaxi Song; Xutong Wu; Haoyu Zhang (International Journal of Applied Earth Observations and Geoinformation, 2024)
China’s oases are the center of human life and economic development for tens of millions of inhabitants in drylands. However, oases have experienced a significant expansion of cropland during the past three decades, which has resulted in rapidly increasing agricultural water demand and increasing water shortages in the region. Although crop switching is recognized as a promising strategy for improving the sustainability of agricultural production, little is known about how much it can improve the sustainability of oasis cropping systems and whether there are trade-offs among multiple sustainability goals. Here, we used a crop-water-use model, data on crop production and nutrient content, observational data on streamflow, and oasis land-use data to assess the impacts of different crop switching scenarios on water demand, nutrient supply, and income. The results showed that oasis agricultural water demand increased from 28.5 km3 to 41.1 km3 between 1987 and 2017, with 74.6 % of the oasis counties experiencing increasing agricultural water stress. By replacing all crops with those having the lowest water demand in each respective county, the demand for irrigation can be reduced by 23.1 %, and the demand for groundwater reduced by as much as 72.8 %. Crop switching scenarios that also consider crop species diversity, in which replacing the highest water demand crops with alternative crops (those with the lowest water demands, highest protein production, or highest calorie production) in each county can effectively reduce irrigation water demand (8.5–12.9 % for streamflow and 32.7–43.3 % for groundwater), while increasing protein (21.3–35.8 %) and calorie (27.5–42.7 %) production as well as income (1.4–2.4 %). Our research provides potential solutions to effectively alleviate the conflict between agricultural development and the environment in oasis regions.